106: DOUBLE TRACT RECONSTRUCTION VS POSTERIOR ESOPHAGO-GASTROSTOMY WITH PARTIAL NEO-FUNDOPLICATION AFTER PROXIMAL GASTRECTOMY IN ADVANCED GASTRIC CANCER. (23rd April 2022) - Sedlak, K; Rawicz-Pruszynski, K; Geca, K; Mlak, R; Polskowski, W
Abstract: Background and aim: There is an upward shift in the incidence and localization of gastric cancer (GC). Proximal gastrectomy (PG) has been advocated as an alternative operation for the upper third GC that may be performed as a function-preserving procedure with various new reconstruction techniques. Uneventful postoperative course is currently measured using well-defined textbook outcome (TO), which represents a composite of surgical quality metrics. The aim of this report was to compare the TO of the two reconstruction methods following PG: double tract reconstruction (DTR) and posterior esophago-gastrostomy with partial neo-fundoplication (EGF). Methods: TO was defined as (1) radical resection according to the surgeons' assessment at the end of the operation, (2) no intraoperative complications, (3) negative resection margins, (4) harvest of min. 15 lymph nodes (5) no severe postoperative complications, (6) no re-interventions, (7) no readmission to intensive care unit, (8) no prolonged hospital stay, (9) no hospital readmission and (10) no postoperative mortality. Some 44 patients were eligible for analysis. Results: The DTR and EGF were performed in 21 and 23 patients, respectively. Detailed results of TO in DTR and EGF are shown in Table 1. Patients reconstructed with DTR had a nearly six-fold increased chance of achieving the TO compared to patients with EGF (OR = 5.80; P = 0.0090). Comparison of both reconstruction methods demonstrated no statistically significant differences in terms of postoperative complications and CCI score, and overall survival. Conclusion: TO is more likely to be achieved in DTR than in EGF. Randomized controlled trials are warranted to indicate the preferred reconstruction technique after PG.